Outcome of biliary atresia in Malaysia: a single-centre study - Lee, W.S.; Chai, P.F.; Lim, K.S.; Lim, L.H.; Looi, L.M.; Ramanujam, T.M. (Wiley, 2009)
This study aimed to determine the outcome of the operation of children with biliary atresia (BA) at a tertiary paediatric referral centre in Malaysia. A prospective study on all patients with BA referred to the University of Malaya Medical Centre (UMMC), Kuala Lumpur, from 1996 to 2005 was conducted. Survival with native liver, liver transplantation (LT) or death at 2 years of age was determined. The median age at referral of the 57 patients with BA seen at University of Malaya Medical Centre was 62 days. Kasai procedure was not performed in nine patients who were all referred late (median age of referral 180 days). The median age at hepatoportoenterostomy (HPE) of the remaining 48 patients was 70 days. A total of 53 (93) patients had type 3 BA, while only 1 (2) patient had BA splenic malformation. At 2 years, the survival rate with native liver for the 48 patients who had HPE was 37, while the overall survival (native liver and LT) rate was 40. Two of the four patients who had LT survived with a liver graft at 2 years. The 2-year survival with native liver following corrective surgery for BA in UMMC, Malaysia, compares favourably with other international figures, but the overall survival rate was adversely affected by a lack of timely LT. The outcome of BA in Malaysia may be further improved by increasing the awareness among child-health professionals on the importance early referral for appropriate surgery in infants suspected of having BA.